Training Quality as a Dynamic Construct: Longitudinal Evidence of Changing Effects on Vocational Competence Development - Viola Deutscher; Beifang Ma; Maximilian Kroetz; Esther Winther (Vocations and Learning, 2026)
Background: Recent research has increasingly explored instructional quality in shaping Vocational Education and Training (VET) outcomes. However, how instructional quality in company-based training influences vocational competence development remains unclear, particularly regarding its dynamic effects at different training stages. Aims: This study examines how training quality criteria and individual trainee characteristics influence the development of general and domain-specific competence over two years of VET. Sample: The study followed 458 commercial trainees throughout their VET program. Methods: Training quality was assessed via questionnaires, and competence was measured using validated tests at three points: program start, midpoint, and end. Latent Growth Modeling (LGM) was used to analyze growth trajectories, incorporating time-invariant (e.g., prior education) and time-varying predictors (e.g., feedback). Results: Four training quality criteria (task relevance, autonomy, feedback, school-company cooperation) and four individual characteristics (age, prior education, literacy interest, desired occupation) significantly fostered competence development, albeit at varying stages. Conclusions: The findings emphasize the dynamic nature and varying impact of training quality on competence development and the critical importance of tailoring strategies to specific competence dimensions and training phases. Adopting a nuanced, adaptive approach to training design can significantly enhance outcomes in VET contexts. This requires accounting for individual characteristics, comprehensively addressing various aspects of training quality, and distinguishing clearly between different types of competence.
Keywords: 370; Workplace Learning Environment; Vocational Training; Quality; Competence; Sensitivity